Ethical Implications of End-Of-Life Decisions - Nemetz, Elisheva; Huang, Ryan (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
This paper examines the recent policy update by the College of Physicians and Surgeons of Ontario (CPSO), which allows physicians to override patient wishes for cardiopulmonary resuscitation (CPR) without consent. It critically analyzes the ethical implications of this shift, emphasizing the juxtaposition between the legal protections for patient’s Last Wills and the relatively diminished safeguarding of their end-of-life care preferences. The paper highlights the potential for bias in physician decision-making, the risk of reverting to a more paternalistic healthcare model, and the challenge of balancing patient autonomy with medical authority. The study underscores the need for a nuanced approach to healthcare policy that respects patient autonomy while addressing the complexities of end-of-life decisions.